Campus, academics and cultural engagements: A perception study among international students in an HEI in Mumbai, India - Balasubramanian, Jayashree (Taylor & Francis, 2025)
Internationalization and sharing of knowledge takes place in both the directions inward and outward. Easy mobility of staff, faculty, and students contribute to the enrichment of the intellectual environment of the institutions involved. Fee paying, degree-seeking students also contribute to the financial health of the institutions they are enrolled in. Though internationalization has its meaning beyond economic rationale, it may be defined as the intentional process of integrating an international, intercultural, or global dimension into the purpose, functions and delivery of post-secondary education, in order to enhance the quality of education and research for all students and staff, and to make a meaningful contribution to society (Knight, 2004).
ISME